2009
DOI: 10.3109/00016480902725254
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent changes in the expression of klotho protein, TRPV5 and TRPV6 in mouse inner ear

Abstract: Immunostaining for klotho was observed in stria vascularis, outer and inner hair cells (OHCs and IHCs), and in vestibular sensory cells and dark cells, and less intensely in the spiral and vestibular ganglion cells. Expression of TRPV5 was found in stria vascularis, organ of Corti, vestibular sensory cells and dark cells, and less intensely in the spiral and vestibular ganglion cells. Expression of TRPV6 was found in supporting cells of the organ of Corti, with weak labelling in OHCs and IHCs. Weak fluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 18 publications
3
24
0
Order By: Relevance
“…Both TRPV5 and TRPV6 were shown to be expressed in the vestibular dark cells and in the epithelial cells of the semicircular canal duct epithelium (50,51). The abolished calcium reabsorbance of these channels leads to elevation in calcium levels in the endolymph to which the utricle is exposed.…”
Section: Initial Formation Of Giant Calcium Carbonate Stones In Slc26a4mentioning
confidence: 99%
“…Both TRPV5 and TRPV6 were shown to be expressed in the vestibular dark cells and in the epithelial cells of the semicircular canal duct epithelium (50,51). The abolished calcium reabsorbance of these channels leads to elevation in calcium levels in the endolymph to which the utricle is exposed.…”
Section: Initial Formation Of Giant Calcium Carbonate Stones In Slc26a4mentioning
confidence: 99%
“…Notably, TRPA1 has been suspected as a component of mechanotransduction channels at the hair bundles of sensory hair cells [55,56]. In SGNs, TRP receptors have been shown to be expressed in the cell body by immunohistochemistry: TRPV1-6 [57][58][59], TRPC1-7, more intensely in TRPC1 and TRPC3 [60,61], TRPM1, 2, 3, 6, 7, and 8 [62], TRPML1-3, TRPP2, 3, and 5 [63]. Modified expression of TRPV was reported following cochlear damage.…”
Section: Neuromodulation In Sgn/vgnmentioning
confidence: 99%
“…Due to the distribution of klotho close to the Na-K-Cl co-transporter and the involvement of klotho with other proteins that regulate calcium homeostasis, e.g., transient receptor potential (TRPV), it was suggested that klotho participates in the regulation of the ionic composition of the endolymph; furthermore, the expression of klotho in the inner-ear sensory cell of the mouse led to the hypothesis that klotho is involved in signal transduction in the inner ear (Takumida et al, 2009). The expression of klotho was found to be closely related to the lifespan of the organism and klotho seems to have a protective effect against oxidative stress and to increase cell resistance to the subsequent damage (Yamamoto et al, 2005;Ikushima et al, 2006).…”
Section: Geneticsmentioning
confidence: 99%
“…Klotho is expressed predominantly in tissues involved in the regulation of calcium homeostasis and was found in the stria vascularis and the vestibular dark cells of the inner ear (Kamemori et al, 2002;Takumida et al, 2009). Due to the distribution of klotho close to the Na-K-Cl co-transporter and the involvement of klotho with other proteins that regulate calcium homeostasis, e.g., transient receptor potential (TRPV), it was suggested that klotho participates in the regulation of the ionic composition of the endolymph; furthermore, the expression of klotho in the inner-ear sensory cell of the mouse led to the hypothesis that klotho is involved in signal transduction in the inner ear (Takumida et al, 2009).…”
Section: Geneticsmentioning
confidence: 99%